Implementation of Clustering Methods to Know Electricity Energy Sold Average Customer Type - Reinhard Oktaveri Gultom; Estomih Wau; Jodi Alexsander Laia; Ivan Leonardo Silaban; Yennimar Yennimar (Institute of Computer Science (IOCS), 2021)
The need for electrical energy in Indonesia continues to increase from time to time. In realizing the need for electrical energy, it is important to order electrical energy based on the type of customer. In collecting this electrical energy, grouping is needed. The results of the gathering can be utilized by PT. PLN to anticipate disruptions in the supply of electrical energy. This investigation plans to determine the electrical energy sold by type of customer (KWH) in 2016 to 2019 in Indonesia and dissect the power requirements in 2019. The strategy used is group development using rapidminner. The variables that cause the utilization of the tourism industry in Indonesia are Population, Economic and Industrial Developments. To meet the need for the use of electrical energy which continues to increase from year to year, the matters and groupings of the use of electrical energy for the use of electrical energy were completed in 2014 to 2019. The information and targets used in the meeting were gross domestic electricity, group information and power information. (per customer type and power utilization). from 2011 to 2015. The side effect of ordering electrical energy in Indonesia using the fuzzy bunching strategy was 272,630 KWH in 2019, an increase of 85,089 KWH with an annual normal increase of 6.96%. the result group of the strategy has a normal of 18,730 KWH against RUPTL.